2022
DOI: 10.1055/a-1964-8538
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Oral Inflammation in Elite Sports: A Narrative Review

Abstract: Recently, there has been intense discussion about sports dentistry and potential interactions between oral health and athletes’ performance. This narrative review aims to provide a comprehensive overview of the available literature about oral inflammation in sports. For this purpose, it presents the most common types of oral inflammation (gingivitis, periodontitis, pericoronitis, apical periodontitis), and their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…We found that the possibility of periodontitis was higher in young adults with moderate intensity PA levels <150 min/wk, which is below the level suggested by the American guideline for cardiovascular health. 11 In addition, there were no additional benefits for the lower prevalence of periodontitis if the moderate intensity PA levels were over 300 min/wk. The benefits of PA on periodontitis may be offset by an increased risk of periodontitis in highly fit individuals, i.e., athletes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that the possibility of periodontitis was higher in young adults with moderate intensity PA levels <150 min/wk, which is below the level suggested by the American guideline for cardiovascular health. 11 In addition, there were no additional benefits for the lower prevalence of periodontitis if the moderate intensity PA levels were over 300 min/wk. The benefits of PA on periodontitis may be offset by an increased risk of periodontitis in highly fit individuals, i.e., athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of PA on periodontitis may be offset by an increased risk of periodontitis in highly fit individuals, i.e., athletes. 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a behavioral perspective, athletes may place greater focus on improving physical fitness and ignore other aspects of health including oral care. Periodontal disease could arise due to poor compliance with dental appointments and oral hygiene instruction (64), as well as frequent consumption of carbohydrate-rich sports drinks which have been associated with higher BPE scores (21). Finally, as several of the studies on elite athletes' periodontal conditions collected data in the lead up to or during high profile athletic events such as the Olympics (53, 55) and regional championships (52), the impact of psychological stress in the athletes surveyed should be considered when interpreting these results.…”
Section: Periodontal Conditions Of Elite Athletesmentioning
confidence: 99%